ANALISIS NILAI TAMBAH DAN KEMAMPULABAAN TIGA AGROINDUSTRI VCO D1 KOTA BENGKULU - Nabiu, Musryadi; Yuliarti, Ellys; Manurung, Esteria (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2006)
This research was did on Bengkulu town at June until July 2006 with purpose to know how many VCO agroindustry can create the value added, profit level and efficiency level of production cost structure from 3 VCO industries in Bengkulu town. Location Determination Method is by purposive with reason that VCO agroindustri in Bengkulu town have existing and property commercial. Respondent determination method is by purposive, sum samples in this research are three VCO agro industry. Data used in this research, are primary and secondary. analysis method in this research are value added of processing, Break Event Point (BEP) and profltability.Analisis yield Value Added processing 1 grain coconut processing are VCO Dara 2.5761Btr, NeoVico Rp 2.05218tr and VCO Raffesia Rp 2. 1951Btr.Total high more fix cost are VCORaffesia Rp 1.548.747 (57,72 %) / pp, and VCO Dara Rp 609.413 (22,7 %)/pp and than low is rank fix cost